IMPACT OF EXTENSIVE READING ON SOPHOMORE ENGLISH MAJORS’ READING COMPREHENSION DEVELOPMENT AT DALAT UNIVERSITY - Nguyen, Thi Thao Hien (Trường Đại học Đà Lạt, 2023)
This paper reports on an extensive reading program utilizing graded readers and the Moodle Reader for sophomore English majors at Dalat University. The main purpose of the study was to determine the impact of such a program on student reading abilities and to explore their attitudes toward the program. Data were collected from pretests, posttests, and questionnaires. Findings indicated that the extensive reading program was largely responsible for the higher mean gain on the posttest made by the experimental group, and that the majority of students expressed positive opinions toward the program. The paper concludes by putting forward some pedagogical implications on the implementation of such a program with English language students and lecturers in their courses of reading.